STUDY ON THE ROLE OF MOSQUE LIBRARIES IN THE DISSEMINATION OF ISLAMIC KNOWLEDGE IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Emir Khaddafi; Hasan Hasan (JURNAL ILMU PERPUSTAKAAN (JIPER), 2024)
The research discusses the role and function of libraries in Islamic places of worship, specifically mosques, for the community or mosque visitors. The community here is categorized as people who visit the mosque, such as school children, teenagers, and adults. The aim of this research is to explain the extent of the role and function of mosque libraries for their users, who are predominantly Muslim. This study employs a qualitative research design with the Systematic Literature Review (SLR) method. The SLR is conducted for various purposes, including identifying, reviewing, evaluating, and interpreting all available research on a particular phenomenon with specific and relevant research questions.The results of the study indicate that mosque libraries serve as agencies for the community, as public spaces for sharing knowledge, selecting and synthesizing information, conducting research, and developing knowledge. They also act as partners in carrying out da'wah (Islamic outreach) and play a role in character education and community development. The collections provided are diverse and have been carefully selected, including the Qur'an, Hadith, and Tafsir (interpretations of the Qur'an), collections on fiqh (Islamic jurisprudence) and aqidah (creed), sirah (biographies of the Prophet), and even fictional works such as novels and comics related to Islam. Additionally, there are bulletins, manuscripts, magazines discussing Islamic topics, as well as audio and video collections about Islam